Going all in on college counseling: Successes and trade-offs. (October 2019) - Ilic, Gorana; Rosenbaum, James E.
While many high schools reproduce social inequalities in college access, little is known about the schools that successfully reduce them. To this end, Gorana Ilic and James E. Rosenbaum studied an urban high school that expressed a strong commitment to supporting all students' college applications. In this article, they describe the organizational conditions and supports that enabled the school's counselors to achieve ambitious college-enrollment rates, and they consider what sacrifices and challenges might have emerged in the process and ways to address these challenges .